2011
DOI: 10.1111/j.1365-2249.2011.04440.x
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome in health and disease: the good, the bad and the ugly

Abstract: While interleukin (IL)-1β plays an important role in combating the invading pathogen as part of the innate immune response, its dysregulation is responsible for a number of autoinflammatory disorders. Large IL-1β activating platforms, known as inflammasomes, can assemble in response to the detection of endogenous host and pathogen-associated danger molecules. Formation of these protein complexes results in the autocatalysis and activation of caspase-1, which processes precursor IL-1β into its secreted biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
323
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(342 citation statements)
references
References 202 publications
(177 reference statements)
4
323
0
15
Order By: Relevance
“…Production of IL-1␤ strongly depends on the function of multiprotein complexes called inflammasomes. Among inflammasomes, one of the most intensively studied ones is the Nlrp3 inflammasome that contains an Nlrp3 sensor, an ASC adaptor and a caspase-1 enzyme (Cassel et al, 2009;De Nardo and Latz, 2011;Menu and Vince, 2011). Due to its critical function in inflammatory responses, and as part of the safety feature of the immune system, IL-1␤ production is regulated at various levels and requires distinct signals.…”
Section: Introductionmentioning
confidence: 99%
“…Production of IL-1␤ strongly depends on the function of multiprotein complexes called inflammasomes. Among inflammasomes, one of the most intensively studied ones is the Nlrp3 inflammasome that contains an Nlrp3 sensor, an ASC adaptor and a caspase-1 enzyme (Cassel et al, 2009;De Nardo and Latz, 2011;Menu and Vince, 2011). Due to its critical function in inflammatory responses, and as part of the safety feature of the immune system, IL-1␤ production is regulated at various levels and requires distinct signals.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Evidence supports that the aberrant activation of the NLRP3 inflammasome is associated with the pathogenesis of various autoinflammatory, autoimmune, and chronic inflammatory and metabolic diseases, including gout, atherosclerosis, and type 2 diabetes. [13][14][15] Thus, activation of the NLRP3 inflammasome should be tightly regulated to prevent unwanted host damage and excessive inflammation. To date, several regulatory mechanisms and binding partners have been described in NLRP3 inflammasome activation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that inflammation plays a key role in the pathophysiology of myocardial I/R injury 1, 3. Increasing evidence also indicates that a sterile inflammatory response triggered by tissue damage is mediated through a multiple‐protein complex called the inflammasome 4, 5. It is known that nucleotide‐binding oligomerization domain‐Like Receptor with a Pyrin domain 3 (NLRP3) inflammasome are formed after myocardial I/R injury and the subsequent activation process could lead to the interleukin‐1β production 6, 7, which crucially contributes to cardiac ischaemia injury and post‐infarct remodelling.…”
Section: Introductionmentioning
confidence: 99%